STUDENT-COMMUNITY PARTNERSHIP IN IMPROVING HEALTH LITERACY TOWARD NATIONAL HEALTH INSURANCE - Nuzulul Kusuma Putri; Diansanto Prayoga; Syifaul Lailiyah; Ernawaty Ernawaty (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: As of December 2018, BPJS Kesehatan has received application from 4,909 people to be registered as non-contribution assistance beneficiary (PBPU) through Gandrung JKN. Number of people to be registered to BPJS as non-contribution assistance beneficiary (PBPU) tends to fluctuate every month and tends to be stagnant in several districts, including in Licin Subdistrict. Most of people in Licin Subdistrict also not familiar with Gandrung JKN program. Objective: This student-community partnership is carried out to minimize the gap in community knowledge about what JKN is and the procedure to be registered in JKN scheme.  Method: The role of students in the effort to introduce and register the community in JKN was designed by bringing the community closer to the Banyuwangi Gandrung Program. This community service consists of three stages, including activities in provisioning the students and health cadres about JKN and Gandrung JKN, direct socialization by students in the Licin subdistrict community, and efforts to provide closer access of community to BPJS Kesehatan.  Results: The debriefing in the first stage was given directly by the Banyuwangi Branch BPJS Kesehatan to increase students' knowledge of JKN. Students then successfully carried out direct socialization to the Licin subdistrict community. Three villages were successfully accompanied and performed a high level of participation in the socialization session. Community service has also succeeded in bringing people closer to BPJS Kesehatan. Conclusion: The information conveyed in this activity was well received by the community because it was tailor-made according to the information needed by each family. Student assistance sharpens students' ability to communicate and understand JKN. Although the assistance succeeded in increasing the community's knowledge, in the short term it did not significantly increase the desire to register to become a JKN participant.